Polyphenols mitigating inflammatory mechanisms in Inflammatory Bowel Disease (IBD): focus on NF-κB and JAK/STAT pathways - Ismail, Elysha Nur; Vidyadaran, Sharmili; Othman, Zulkefley; Muhamad Zakuan, Noraina; Ishak, Reezal; Mohammad, Hussin (Springer, 2024)
The term "inflammatory bowel disease" (IBD) refers to a group of chronic inflammatory gastrointestinal disorders, which include ulcerative colitis and Crohn's disease. The necessity for alternative therapeutic approaches is underscored by the fact that, although present medicines are successful, they frequently result in considerable adverse effects. Naturally occurring substances included in fruits and vegetables called polyphenols have been shown to have the capacity to control important inflammatory pathways including NF-κB and JAK/STAT, which are essential to the pathophysiology of IBD. The processes by which polyphenols, such as curcumin, EGCG, resveratrol, and quercetin, reduce inflammation are examined in this article. Polyphenols may have therapeutic advantages by blocking the synthesis of cytokines and the activation of immune cells by targeting these pathways. Preclinical study indicates a reduction in intestinal inflammation, which is encouraging. However, more clinical research is needed to determine the clinical relevance of polyphenols in the therapy of IBD, especially with regard to their long-term safety and bioavailability